The sapphire sea - Bunn, T. Davis, 1952- (Bunn, T. Davis, 1952- Outer Banks series, 2026)
Being himself is a challenge . . . When it comes to the bittersweet memories of his late mother, Colin Eames is a relatable boy, recalling her tales of a faraway place called the Sapphire Sea where happiness forever is a way of life. Other than that, Colin is different. To Child Services, he is a prodigy to be nurtured. To his classmates, he's an outsider. To his father, a man of political ambitions and unchecked rage, Colin is a trial, defying the narrowed path his father demands. When Colin is accepted into the Outer Banks Academy for the Gifted, it's his chance to slip out from under his father's control, to chart his own course, and to embark on a quest for the one thing that eludes him: love. Understanding himself is a wonder . . . As the years pass and Colin's freedom offers dream opportunities, his yearning to make a connection grows stronger. It's a difficult longing for an awkward teenager for whom the simplest interactions are a mystery. Then he meets Mira, an empathic girl weathering tragic losses of her own. She's there for him, supporting each new step he takes. Even those with Tiana, a history student from Hawaii who ushers Colin into a new world of first kisses, belonging, and trust--far from the confusion and loneliness of his childhood days. For Colin, maybe the promise of the Sapphire Sea wasn't a bedtime story after all, but rather a true and genuine place in the heart--one worth searching and waiting for..